Utilization pumpkin ( (curcubita moschata durch) as a color enhancer for Nile tilapia (oreochromis niloticus) dry noodles - Nelsi Fibentia; Dahlia '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was intended to evaluate the effect of pumpkin on the color of Nile Tilapia noodles. Four types of dry noodles were prepared from a mixture of wheat flour (60,3%), soda ash (0,9%), salt (0,3%), water (22,3%), egg (9,5%), carboxy methyl cellulose (0,6%), Nile tilapia meat (6,0%); and the mixture was added with pumpkin paste at a level of 0%, 10%, 20% and 30% counted from wheat flour weight. The noodles were evaluated for color, odor, texture, taste , moisture, protein, ash and total bacterial count. The result showed that the color, taste and odor value of the noodles improve until the addition of pumpkin up to 20%, but the texture was decreased. Moisture of dry noodles which added with 0%, 10%, 20% and 30% yellow gourd was 9,61%, 8,24%, 7,85%, 6,29%respectively; protein was 28,98%, 27,46%, 23,94%, 20,28%respectively; ash was 1,48%, 1,55%, 1,62%, 1,72% respectively; bacterial count was 3,7x105 sel/g, 3x105 sel/g, 1,8x105 sel/g, 1,6x105 sel/g respectively.Keyword: Dry noodles, Pumpkin (Curcubita moschata durch), Nile tilapia (Oreochromis niloticus).